Mindful Money: The Impact of Financial Literacy, Lifestyle, and Social Influence on Responsible Spending Among University Students - Kee, Daisy Mui Hung; Qi, Ng Chin; Huan, Ng Chee; Torng, Ng Fei; Subramaniam, Navaranjitha A/P (The Global Academia Publisher, 2025)
Spending behavior has become a significant concern as many individuals face financial difficulties and even bankruptcy due to poor financial management. In Malaysia, the government has increasingly emphasized the importance of financial literacy among undergraduate students to address these issues. This study investigates the impact of financial literacy, lifestyle choices, social influence, materialism, and financial attitudes on responsible spending behavior among university students. Specifically, it explores how these factors influence financial attitudes and whether financial attitudes, in turn, affect responsible spending behavior. Data collected from 180 university students in Malaysia revealed that financial literacy, lifestyle choices, and social influence positively impact financial attitudes and responsible spending behavior, while materialism has a negative effect. Moreover, financial attitudes were found to influence responsible spending behavior. Our findings highlight that financial literacy, lifestyle choices, and social influence positively affect both financial attitudes and responsible spending behavior, while materialism has a negative impact. Financial attitudes also play a key role in shaping responsible spending among university students.